Hubungan antara Perdagangan Global dan Ketahanan Ekonomi Indonesia pada sektor Pariwisata - Rizki Apriansyah; Enjum Jumhana; M Ilham Kurniawan; Rizqi Ardiansyah; Ridho Ilhami (Journal Economic Excellence Ibnu Sina, 2025)
Tourism is one of the sectors that has a major impact on economic growth in Indonesia, both in terms of state revenue and continuing to expand employment opportunities. In terms of global trade, the tourism sector is greatly influenced by international economic dynamics, such as the flow of foreign tourists, trade policies, and global economic stability. This study aims to analyze the relationship between global trade and Indonesia's economic resilience in the tourism sector, focusing on facing global turmoil such as pandemics, trade wars, and financial crises. The method used is a quantitative approach with secondary data analysis from BPS reports, related ministries, and global trade organizations. The results of the study show that there is a strong relationship between global trade growth and the performance of the tourism sector, as well as the important role of this sector in stabilizing national economic resilience through diversification of foreign exchange sources and increasing gross domestic product (GDP).